2012
DOI: 10.1186/1477-5956-10-30
|View full text |Cite
|
Sign up to set email alerts
|

Development stage-specific proteomic profiling uncovers small, lineage specific proteins most abundant in the Aspergillus Fumigatus conidial proteome

Abstract: BackgroundThe pathogenic mold Aspergillus fumigatus is the most frequent infectious cause of death in severely immunocompromised individuals such as leukemia and bone marrow transplant patients. Germination of inhaled conidia (asexual spores) in the host is critical for the initiation of infection, but little is known about the underlying mechanisms of this process.ResultsTo gain insights into early germination events and facilitate the identification of potential stage-specific biomarkers and vaccine candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 81 publications
4
61
1
1
Order By: Relevance
“…The alignment results were also edited using the Jalview 2.8 tool (49) for enhanced visual presentation. To find the metabolic enzymes responsible for the xylose and cellobiose degradation, we used the XYL1, XYL2, and XYL3 proteins of P. stipitis (50,51) as well as BGLs of A. niger (BGL1; Q30BH9) (52), A. fumigatus (BTGE; B0Y9Q9) (53), and Candida wickerhamii (BGLA; Q12602) (54) as the templates. We further applied the PSORTII tool (55) to predict the cellular localization of the BLASTPsearched putative BGL genes of Y. lipolytica.…”
Section: Strains and Plasmidsmentioning
confidence: 99%
“…The alignment results were also edited using the Jalview 2.8 tool (49) for enhanced visual presentation. To find the metabolic enzymes responsible for the xylose and cellobiose degradation, we used the XYL1, XYL2, and XYL3 proteins of P. stipitis (50,51) as well as BGLs of A. niger (BGL1; Q30BH9) (52), A. fumigatus (BTGE; B0Y9Q9) (53), and Candida wickerhamii (BGLA; Q12602) (54) as the templates. We further applied the PSORTII tool (55) to predict the cellular localization of the BLASTPsearched putative BGL genes of Y. lipolytica.…”
Section: Strains and Plasmidsmentioning
confidence: 99%
“…Furthermore, T cell Ags in the metabolically active A. fumigatus morphotypes were largely overlapping, which is in line with recent results on the proteomic signature of A. fumigatus during early development. These studies showed that the majority of mycelial proteins are also present in all early, metabolically active morphotypes, and only their abundance varied (20,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Tris or phosphate buffers at 10 -30 mM were used to keep the pH constant and/or to be compatible with DIGE-labeling [22]. Further, the addition of NaOH at 0.1 -1 M can enhance the protein solubility and destabilize the cell wall tremendously [23]. As a non-ionic detergent CHAPS is used at the concentrations of 1% -4%.…”
Section: Sample Homogenisationmentioning
confidence: 99%